2013
DOI: 10.1111/hepr.12099
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐finding trial of tolvaptan in liver cirrhosis patients with hepatic edema: A randomized, double‐blind, placebo‐controlled trial

Abstract: Tolvaptan at 7.5 mg/day was considered the optimal dose in liver cirrhosis patients with hepatic edema who showed inadequate response to conventional diuretics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 23 publications
4
73
0
Order By: Relevance
“…Among them, tolvaptan (7.5-30 mg/day for 7 days) showed add-on effects to conventional diuretics on ascites in multicenter RCTs for poor responders to the standard diuretic therapy (furosemide at 40 mg/day or greater and spironolactone at 25 mg/day or greater; or furosemide at 20 mg/day or greater and spironolactone at 50 mg/day or greater) [150,151]. As a dosage of 7.5 mg/day showed the maximum effects with preferable tolerability [151] and a dosage of 3.75 mg/day also exerted significant effects [152], the proper dosage was determined as 3.75-7.5 mg/day. The effects were unrelated to serum albumin levels [150].…”
Section: Cq: Is Albumin Infusion Effective For Treatment Of Cirrhoticmentioning
confidence: 99%
“…Among them, tolvaptan (7.5-30 mg/day for 7 days) showed add-on effects to conventional diuretics on ascites in multicenter RCTs for poor responders to the standard diuretic therapy (furosemide at 40 mg/day or greater and spironolactone at 25 mg/day or greater; or furosemide at 20 mg/day or greater and spironolactone at 50 mg/day or greater) [150,151]. As a dosage of 7.5 mg/day showed the maximum effects with preferable tolerability [151] and a dosage of 3.75 mg/day also exerted significant effects [152], the proper dosage was determined as 3.75-7.5 mg/day. The effects were unrelated to serum albumin levels [150].…”
Section: Cq: Is Albumin Infusion Effective For Treatment Of Cirrhoticmentioning
confidence: 99%
“…Although diuretics, such as loop diuretics, are the standard treatment for hepatic ascites, loop diuretics can induce renal dysfunction and hyponatremia [5, 6]. The vasopressin V2 receptor antagonist, tolvaptan, which was developed in Japan, was shown effective in 50–60% of cirrhotic patients with ascites refractory to conventional diuretics [7-9]. A meta-analysis also found that vasopressin V2 receptor antagonists improved hyponatremia and may improve symptoms in cirrhosis patients with refractory ascites [10].…”
Section: Introductionmentioning
confidence: 99%
“…Arginine vasopressin receptor antagonists, a novel class of diuretics, have been recently approved for the treatment of cirrhosis-related fluid retention in Japan (3,4). These diuretics antagonize vasopressin V2 receptors, resulting in the inhibition of electrolyte-free water reabsorption and an increase in electrolyte-free water excretion (5).…”
Section: Introductionmentioning
confidence: 99%